S100 calcium-binding protein A8 exacerbates deep vein thrombosis in vascular endothelial cells - Junyu Chi; Qitao Wang; Zhen Wang; Wenjie Zeng; Yangyang Gao; Xin Li; Wanpeng Wang; Jiali Wang; Ming Qu (Scientific Reports)
Abstract Previous studies highlighting the pivotal function of the S100A8 protein have shown that inflammation and vascular endothelial harm play a major role in deep vein thrombosis (DVT) development, as evidenced by earlier studies highlighting the pivotal function of the S100 calcium-binding protein A8 (S100A8). Therefore, we aimed to establish a connection between S100A8 and DVT and investigate the role of S100A8 in DVT development. Blood specimens were taken from 23 patients with DVT and 31 controls. The fluctuation and association for S100A8 and interleukin-1 beta (IL-1β) in the specimens was assessed using enzyme-linked immunosorbent assay. We also used the human recombinant protein S100A8 to activate human umbilical vein endothelial cells and created a rat model to explore the possible relationship between them. Studies have shown that the infiltration of S100A8 sustains local inflammation and thrombus formation, which may exacerbate DVT by amplifying NLRP3/Caspase-1/IL-1β signals in the vascular endothelial cells.